2023
DOI: 10.1186/s12933-023-01759-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the stress hyperglycemia ratio and severity of coronary artery disease under different glucose metabolic states

Abstract: Background Stress hyperglycemia ratio (SHR) is significantly related to adverse cardiovascular clinical outcomes and increased in-hospital mortality. However, the relationship between SHR and coronary artery disease (CAD) severity has hitherto not been reported. This study sought to clarify the relationship between the SHR and CAD severity of individuals with different glucose metabolic statuses. Methods A retrospective analysis was performed on 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This study identified that, alongside CPET parameters, factors like age, HDL levels, hypertension, and diabetes mellitus independently predict intermediate-high SS in CAD patients. The OR for age was 1.053, consistent with findings reported by Zhang et al 25 Notably, HDL emerges as a protective factor against CAD, indicating that lower HDL levels in CAD patients may correlate with more severe disease, 26 , 27 echoing prior research on the significant impact of abnormal lipid metabolism on CAD progression. 28 Additionally, hypertension and hyperglycemia are well-established risk factors for adverse cardiovascular events.…”
Section: Discussionsupporting
confidence: 87%
“…This study identified that, alongside CPET parameters, factors like age, HDL levels, hypertension, and diabetes mellitus independently predict intermediate-high SS in CAD patients. The OR for age was 1.053, consistent with findings reported by Zhang et al 25 Notably, HDL emerges as a protective factor against CAD, indicating that lower HDL levels in CAD patients may correlate with more severe disease, 26 , 27 echoing prior research on the significant impact of abnormal lipid metabolism on CAD progression. 28 Additionally, hypertension and hyperglycemia are well-established risk factors for adverse cardiovascular events.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, our study revealed that patients with high SHR and low LVEF had a worse prognosis compared to other groups. This observation is supported by several studies where SHR was correlated with worse LV mechanics, myocardial damage, and disease severity [ 18 , 22 , 36 ]. This evidence implies that elevated SHR might play a pivotal role in the core pathological mechanisms of HFpEF, potentially serving as an indicator of disease severity.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, the association with the SHR seems to be different in CHD patients with differing glycaemic status (NG, prediabetes, and T2DM). Zhang et al conducted a retrospective cohort with 987 CHD patients and reported that a high SHR correlated with the improved risk of multivessel CHD in the prediabetes and DM groups, but this correlation was not significant in patients with NG [ 8 ]. Similar to Zhang’s study, we also determined that the predictive value of the SHR for poor prognosis in patients with CTO lesions was especially significant in those with prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%